The Pedagogics Competence of Indonesian Language Education Students as Teacher Candidates in Microteaching - Sarmadan Sarmadan; Fitriyani Hali (AL-ISHLAH: Jurnal Pendidikan, 2021)
The pedagogics competence of Indonesian language education students as prospective professional teachers is needed to improve the quality Indonesian language learning process. This study aimed to describe the pedagogics competence of students as prospective professional teachers in the Indonesian language education study program. This research uses a descriptive method. This study's subjects were all seventh-semester students in the Indonesian language education study program who programmed microteaching courses for the 2020/2021 academic year, totalling 34 students. The research data collection uses a pedagogic ability test through a google form. The percentage of students who have pedagogic abilities is reviewed by each indicator, namely: Indicator I of 11.76%, indicator II of 72.06%, indicator III of 57.35, indicator IV of 23.53, indicator V of 61.76, indicator VI of 79.41, indicator VII of 64.71, indicator VIII is 48.53, and indicator IX is 58.82. Overall, the percentage of achievement indicators obtained is 53.10%. So, it can be concluded in this study that the pedagogic ability of the seventh-semester students in the Indonesian language education study program is in a low category.